Preoperative Left Ventricle End Diastolic Volume Index as a Predictor for Low Cardiac Output Syndrome After Surgical Closure of Secundum Atrial Septal Defect With Small-Sized Left Ventricle - Rahmat, Budi; Dwita, Nurima Ulya; Arya Wardana, Putu Wisnu; Lilyasari, Oktavia (Frontiers in Pediatrics, 2021)
Introduction: Low cardiac output syndrome is one of the postoperative complications that are associated with significant morbidity and mortality after surgical closure of atrial septal defect (ASD) with small-sized left ventricle (LV). This study investigated whether preoperative left ventricular end-diastolic volume index (LVEDVi) could accurately predict low cardiac output syndrome (LCOS) after surgical closure of ASD with small-sized LV. Method: This retrospective cohort study involved adult ASD patients with small-sized LV from January 2018 to December 2019 in National Cardiovascular Center Harapan Kita. Preoperative MRI data to assess the left and right ventricle volume were collected. A bivariate analysis using independent Student's t-test was done. Diagnostic test using receiver operating characteristic (ROC) curve was also done to obtain the area under the curve (AUC) value. The best cutoff point was determined by Youden's index. Result: Fifty-seven subjects were involved in this study [age (mean ± SD) 32.56 ± 13.15 years; weight (mean ± SD) 48.82 ± 12.15 kg]. Subjects who had post-operative LCOS (n = 30) have significantly lower LVEDVi (45.0 ± 7.42 ml/m2 vs. 64.15 ± 13.37 ml/m2; p < 0.001), LVEDV (64.6 ± 16.0 ml vs. 85.9 ± 20.7 ml; p < 0.001), LVSV (38.97 ± 11.5 ml vs. 53.13 ± 7.5 ml; p < 0.001), and LVSVi (27.28 ± 8.55 ml/m2 vs. 37.42 ± 5.35 ml/m2; p < 0.001) compared to subjects who did not have post-operative LCOS (n = 27). ROC analysis showed that the best AUC was found on LVEDVi (AUC 95.3%; 95% confidence interval: 90.6–100%). The best cutoff value for LVEDVi to predict the occurrence of LCOS after surgical closure of ASD was 53.3 ml/m2 with a sensitivity of 86.7% and a specificity of 85.2%. Conclusion: This study showed that preoperative LVEDVi could predict LCOS after surgical closure of ASD with small-sized LV with a well-defined cutoff. The best cutoff value of LVEDVi to predict the occurrence of LCOS after surgical ASD closure was 53.5 ml/m2.